Exploring the Barriers to Clinic-based Screening for Sexually Transmitted Infections (STIs) among Men in Ghana: A Qualitative Study - Kuufaakang Kuunibe, Joseph; Apiribu, Felix; Tienbia Laari, Timothy; Awenabisa Atanuriba, Gideon; Millicent Dzomeku, Veronica; Bubunyo Bam, Victoria; Diji, Abigail Kusi-Amponsah; Boamah Mensah, Adwoa Bemah; Adoliwine Amooba, Philemon; Saeed Mohammed, Rumana; Benni, Esther (Journal of Community Medicine and Health Solutions, 2024)
The burden of sexually transmitted infections (STIs) continues to increase with over one million curable STIs occurring daily worldwide. Sex disparity in the rates of testing for STIs can compromise the efforts to reduce the incidence of STIs. The study aimed to explore the barriers to facility-based screening for STIs among men in Ghana. A qualitative exploratory design was employed in this study. Using a semi-structured interview guide, individual in-depth interviews were conducted among purposively sampled men from November 2019 to January 2020. Data saturation was achieved at the ninth participant. Audio-recorded interviews were transcribed verbatim and analysed thematically through Braun and Clarke’s approach. Four themes emerged from the analyses: (1) lack of privacy from healthcare providers, (2) mistrust of healthcare providers, (3) the burden of handling thoughts of positive status, and (4) fear of stigmatisation. These barriers deterred men from seeking clinic-based screening for STIs. The barriers were multi-factorial and a major hindrance to ensuring that people are aware of their STI status through screening and diagnosis. It is imperative to consider these barriers when designing STI screening interventions and policies to help promote facility-based screening for STIs among men in Ghana.